Epoxidation of styrene by anhydrous hydrogen peroxide over boehmite and alumina catalysts with continuous removal of the reaction water - Choudhary, Vasant R.; Patil, N. S.; Chaudhari, Nitin K.; Bhargava, Suresh Kumar (Journal of Molecular Catalysis A-Chemical, 2005)
Boehmite and alumina (obtained from the boehmite by its calcination at different temperatures 300-900degreesC) are active and stable catalysts for the selective epoxidation of styrene by anhydrous H2O2 to styrene oxide with continuous removal of the reaction water. Influence of the catalyst (boehemite) calcination temperature, H2O2/styrene ratio and catalyst loading on the styrene conversion and selectivity for styrene oxide. phenyl acetaldehyde. benzaldehyde and benzoic acid in the epoxidation has been investigated. In the presence of water. the catalyst shows very poor activity and selectivity in the epoxidation. The catalyst also catalyses H2O2 decomposition and hence has optimum loading for obtaining high-styrene conversion in the epoxidation. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Alumina; anhydrous hydrogen peroxide; boehmite; Epoxidation of styrene; Styrene oxide

Epoxidation of styrene by t-butyl hydroperoxide over gold nanoparticles supported on Yb2O3: effect of gold deposition method, gold loading, and calcination temperature of the catalyst on its surface properties and catalytic performance - Choudhary, Vasant R.; Dumbre, Deepa K.; Patil, N. S.; Uphade, B. S.; Bhargava, Suresh Kumar (Journal of Catalysis, 2013)
Surface properties and epoxidation performance of Au/Yb2O3 catalyst are influenced by the method of gold deposition [viz. deposition-precipitation (DP), homogeneous deposition-precipitation (HDP) or impregnation], gold loading (0.9-6.6 wt%), and the catalyst calcination temperature (400-900 degrees C)]. The catalyst showed the best epoxidation performance when it was prepared by the HDP method and calcined at 500 degrees C. The Au/Yb2O3 catalyst even after calcination at 900 degrees C showed good activity and epoxide selectivity. Both Au-0 and Au3+ surface species were found in the catalyst calcined at 800 degrees C, but only Au-0 species were observed at the lower calcination temperatures (<600 degrees C). The selectivity for styrene oxide increased continuously with the reaction temperature (from 75 degrees C to 97 degrees C) and time (1-5 h), indicating that styrene oxide did not undergo secondary reactions under these conditions. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Au/Yb2O3 catalyst; Epoxidation of styrene; gold nanoparticles; Styrene oxide; tert-Butyl hydroperoxide

Calcium oxide supported gold nanoparticles as catalysts for the selective epoxidation of styrene by t-butyl hydroperoxide - Dumbre, Deepa K.; Choudhary, Vasant R.; Patil, Nilesh S.; Uphade, Balu S.; Bhargava, Suresh Kumar (Journal of Colloid and Interface Science, 2014)
Gold nanoparticles are deposited on basic CaO supports as catalysts for the selective conversion of styrene into styrene oxide. Synthetic methods, gold loading and calcination temperatures are varied to permit an understanding of their influence on gold nanoparticle size, the presence of cationic gold species and the nature of interaction between the gold nanoparticles and the CaO support. Based on these studies, optimal conditions are designed to make the Au/CaO catalyst efficient for the selective epoxidation of styrene. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Au/CaO; Epoxidation of styrene; gold nanoparticles; Homogenous deposition precipitation method; Styrene oxide